THE PROBLEM OF MINOR WORKING CHILDREN IN HELPING TO FULFILL FAMILY NEEDS IN GAMPONG ALUE SEUTUI JEUNIEB DISTRICT BIREUEN DISTRICT - T. Aris Munandar; Rusnawati (Adisam Publisher, 2025)
This research is entitled